EVALUATING THE EFFECTIVENESS OF 2019 EDUCATION REFORMS IN INCREASING TEACHERS’ STATUS IN KAZAKHSTAN - Berligaliyeva, Gulaiym; Umirbekov, Temirlan; Khussainova, Nagima (Nazarbayev University Graduate School of Public Policy, 2024)
This research aims to evaluate the effectiveness of state programs, introduced after 2019, that were implemented to increase teachers’ status in Kazakhstan. Using UNESCO's recommended definition of teachers’ status as an indicator of value and appreciation that teachers receive in society, we then analyze 5 main factors that influence it: level of autonomy, amount of compensation, workload, opportunities for professional growth and entry requirements in the field. Through a comprehensive survey of more than 2 thousands teachers from all across Kazakhstan, we were able to identify teachers’ perception of these factors and their effect on status, gaining valuable insight into their view on state reforms. Even though teachers generally approved of the reforms, especially for increasing the monetary compensation, many mentioned that state efforts have been futile in other directions. Additional interviews with individuals in the field of education gave a ‘voice’ to teachers’ responses, providing us with a conceptual understanding of survey results and detailed information on their opinions. This research has significant implications for policy-makers who can use our findings to evaluate the effectiveness of said state programs and use them for future policy considerations.
Қазақстандағы мұғалімдердің мәртебесін арттырудағы 2019 жылғы білім беру реформаларының тиімділігін бағалау
Keywords: Type of access: Open Access; teacher status; education reforms; increasing teachers' status